Nocturnal Behavior of Clark’s Spiny Lizard (Sceloporus clarkii; Squamata; Lacertilia) in Acaponeta, Nayarit, México - Loc Barragán, Jesús A. (2022)
There are several documented reports of nocturnal activity in reptiles considered exclusively diurnal (Lara- Resendiz 2020, Perry et al. 2008). Clark?s Spiny Lizard (Sceloporus clarkii) is considered a diurnal active species, but there is a single observation of an adult male attempting to feed on moths at night over a two-hour period (Martínez-Méndez et al. 2013). Herein we report on additional nocturnal activities of S. clarkii and include descriptive thermal data.